The membrane immunoglobulin receptor utilizes a Shc/Grb2/hSOS complex for activation of the mitogen-activated protein kinase cascade in a B-cell line. - Kumar, G (1995)
Ligation of membrane immunoglobulin M (mIgM) receptor in the Ramos B-cell line induced tyrosine phosphorylation of several intracellular substrates, including the adaptor protein. Shc. Phosphorylated Shc could be seen to associate with Grb2 in a complex which included hSOS. Inasmuch as hSOS is involved in p21ras activation, we also demonstrated that mIgM ligation activated a Ras-dependent kinase cascade in which sequential activation of Raf-1 and MEK-1 culminates in the activation of p42 mitogen-activated protein (MAP) kinase (ERK-2). The tumour promoter and protein kinase C agonist, phorbol 12-myristate 13-acetate (PMA), also activated Raf-1, MEK-1, and MAP kinase in Ramos cells, but did not induce tyrosine phosphorylation of Shc or Shc/Grb2 association. Okadaic acid, another tumour promoter and serine/threonine phosphatase inhibitor, activated p42 MAP kinase without activating Raf-1 or MEK-1, suggesting the existence of a serine/threonine phosphatase which directly regulates MAP kinase activity.